The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15061511
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Bioavailability of Se from Daily Food Rations and Dietary Supplements

Abstract: Bioavailability refers to a fraction of a substance that is potentially absorbed from the gastrointestinal tract and enters the systemic circulation (blood). This term is related to various substances, including minerals, that are present in a complex matrix of food which is consumed every day as natural products and pharmaceutical preparations, e.g., dietary supplements. The purpose of the study was to assess the bioavailability of Se from selected dietary supplements, with the simultaneous assessment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…The significant influence of the type of diet was proven, and the highest results were observed in models using the basic diet, followed by high-residue and standard diets. It is hard to find a similar study in the literature on the subject to compare the obtained results with those of other authors, but our previous research, performed for Se, also indicated a positive influence of a basic diet on the bioavailability of this element [30]. In general, inorganic forms of Cr are characterized by the lowest values of bioavailability.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The significant influence of the type of diet was proven, and the highest results were observed in models using the basic diet, followed by high-residue and standard diets. It is hard to find a similar study in the literature on the subject to compare the obtained results with those of other authors, but our previous research, performed for Se, also indicated a positive influence of a basic diet on the bioavailability of this element [30]. In general, inorganic forms of Cr are characterized by the lowest values of bioavailability.…”
Section: Discussionmentioning
confidence: 55%
“…The exact procedure that was developed to prepare and reconstruct DFRs was previously described in detail [30]. Briefly, all food products came from the retail market in the Lublin region.…”
Section: Reconstructed Diet Duplicatesmentioning
confidence: 99%
See 3 more Smart Citations